The uncoupled anterior and posterior spinal ligament tension (UAPLT) – An improvement to three-dimensional spring model of adolescent idiopathic scoliosis (AIS) pathogenesis. (July 2021) - Cheng, Yajun; Shi, Yana; Xu, Bing; Yang, Zongde
Abstract: The pathogenesis of Adolescent Idiopathic Scoliosis (AIS) remains unclear. Previous research proposed that ligament laxity is a clinical feature that can be easily overlooked in patients with AIS. We speculated a new hypothesis which is an improvement of our three-dimensional spring model hypothesis of AIS pathogenesis. The tethered string in the spring model stimulates the spinal ligament instead of spinal cord. Spinal overgrowth in the adolescent age leads to higher tension of posterior spinal ligament. And the ligament laxity leads to lower tension of anterior spinal ligament. This uncoupled anterior and posterior spinal ligament tension maybe the key cause of AIS.